The Ability to Read Aloud German Texts - Putri, Nur Amaliyah; Al Ilmul, Syarifah Fatimah; Hasmawati, Hasmawati (Universitas Negeri Makassar, 2022)
Abstract. This research is quantitative descriptive research. This research aims to obtain data and information about the ability to read aloud and the factors that affect the ability to read aloud German texts for 11th Grade Students of SMA Negeri 15 Makassar. Research instruments, in the form of tests and questionnaires, are used to collect data. The tests are divided into reading tests and multiple-choice questions. Furthermore, the collected data are analyzed by making lists of raw scores, making frequency distributions, creating classification tables, looking for the percentage of students' abilities, and then finding out the average score of students. The result of this research indicates that the ability to read aloud German texts for 11th Grade Students of SMA Negeri 15 Makassar is at an average score of 51.93 and is in the poor category because it does not meet the set score criteria of greater than or equal to 75. The most influential factor in students' ability to read aloud is the teacher’s teaching method.Keywords: Reading Ability, Reading Aloud, German Language